POTENSI GEOWISATA DI KAWASAN TELUK CILETUH, SUKABUMI, JAWA BARAT - Hardiyono, Adi; Syafri, Ildrem; Rosana, Mega F.; Yuningsih, Euis Y.; -, Herry; Andriany, Suci Sarah (Bulletin of Scientific Contribution, 2015)
Ciletuh be local Geopark since August 2014, and now towards preparing to become a National Geopark. This geopark is proposed by the government of Sukabumi in 2014. Remains of the geology in this geopark is the emergence of ophiolite complex as a result of fossil tectonic subduction between the Eurasian plate and the Indo-Australian Plate at the age cretasius. Geomorphology tectonic activity form the shape known as the Ciletuh amphitheater, and also the unique shapes result of water erosion that formed the rocks that looks into unique shapes like dragon-stone, frogs-rock, buffalo-stone. etc. There is also the conservation of green turtles and other wild animals such as sea eagles, panthers also conservation Raflesia flowers, Cantigi and mangrove forests to support geopark Ciletuh. Geopark Ciletuh can be divided into four complexes, namely Geoarea Tamanjaya, Geoarea Ciwaru-Mount Rhinos, Geoarea Citisuk-Cikepuh and Geoarea Citirem Ujunggenteng.Some programs geotrek made to visit geoarea either road, or by sea with a boat, also made supporting facilities such as hotels, homestays, local guides and signs.